Woody-plant ecosystems under climate change and air pollution—response consistencies across zonobiomes? - Matyssek, R.; Kozovits, A.R.; Wieser, G.; King, J.; Rennenberg, H. (Tree physiology, 2017)
Forests store the largest terrestrial pools of carbon (C), helping to stabilize the global climate system, yet are threatened by climate change (CC) and associated air pollution (AP, highlighting ozone (O3) and nitrogen oxides (NOx)). We adopt the perspective that CC-AP drivers and physiological impacts are universal, resulting in consistent stress responses of forest ecosystems across zonobiomes. Evidence supporting this viewpoint is presented from the literature on ecosystem gross/net primary productivity and water cycling. Responses to CC-AP are compared across evergreen/deciduous foliage types, discussing implications of nutrition and resource turnover at tree and ecosystem scales. The availability of data is extremely uneven across zonobiomes, yet unifying patterns of ecosystem response are discernable. Ecosystem warming results in trade-offs between respiration and biomass production, affecting high elevation forests more than in the lowland tropics and low-elevation temperate zone. Resilience to drought is modulated by tree size and species richness. Elevated O3 tends to counteract stimulation by elevated carbon dioxide (CO2). Biotic stress and genomic structure ultimately determine ecosystem responsiveness. Aggrading early- rather than mature late-successional communities respond to CO2 enhancement, whereas O3 affects North American and Eurasian tree species consistently under free-air fumigation. Insect herbivory is exacerbated by CC-AP in biome-specific ways. Rhizosphere responses reflect similar stand-level nutritional dynamics across zonobiomes, but are modulated by differences in tree-soil nutrient cycling between deciduous and evergreen systems, and natural versus anthropogenic nitrogen (N) oversupply. The hypothesis of consistency of forest responses to interacting CC-AP is supported by currently available data, establishing the precedent for a global network of long-term coordinated research sites across zonobiomes to simultaneously advance both bottom-up (e.g., mechanistic) and top-down (systems-level) understanding. This global, synthetic approach is needed because high biological plasticity and physiographic variation across individual ecosystems currently limit development of predictive models of forest responses to CC-AP. Integrated research on C and nutrient cycling, O3-vegetation interactions and water relations must target mechanisms' ecosystem responsiveness. Worldwide case studies must be subject to biostatistical exploration to elucidate overarching response patterns and synthesize the resulting empirical data through advanced modelling, in order to provide regionally coherent, yet globally integrated information in support of internationally coordinated decision-making and policy development.